Danny Dynamite - Ure, Jean (Transworld Publishers Ltd, 1998)
When Billy the Skid and his nasty gang of mountain bikers ride into Bodley Street and ride menacingly up and down, Danny and friends are determined to fight back. They know bullies must be stopped - the question is how? After a little thought, Danny comes up with an ingenious plan and enlists the help of the twins, Daisy and Donna. All will be well providing Danny can lure Billy into the spooky graveyard and sprint through like dynamite!
Keywords: Juvenile literature-Fiction